PERLINDUNGAN HUKUM BAGI KREDITUR DALAM PEMBERIAN KREDITTANPA AGUNAN - Agustina Ni Made Ayu Darma Pratiwi SH.,M.Hum; Duwi Aprianti, S.H.,M.H (Jurnal Ilmiah Raad Kertha, 2021)
This paper aims to identify and analyze legal protection for creditors in providing working capital loans without collateral. The writing method used is normative juridical with a statutory approach. Credit in banking activities is the most important activity, because the largest income from bank business comes from income from credit business activities. Banks provide credit based on trust, so that granting credit is giving trust to customers. But what about credit without collateral because credit collateral will provide legal certainty to the bank that the credit will still return by executing the credit guarantee, while unsecured credit provides no guarantee at all. The basic law that we can use is Articles 1131 and 1132, there are explained in detail about the unsecured credit.